(NpROBLEMY KRISTALLOLOGII (B:s (NsBORNIK STATEJ (B/s - (NuRUSOW(B, (NwADIM sERGEEWI^s; (NpU]AROWSKIJ(B, (Nd(B.(N`(B.s; (NnADEVDINA(B, (Nt(B.(Nn(B.s ((NmOSKWA (B:s (Nmgu(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(Nmgu IM(B. (Nm(B. (Nw(B. (NlOMONOSOWA(B., (NgEOLOGI^ESKIJ FAKULXTETs
Keywords: (NkRISTALLOGRAFIQs; (NkRISTALLOHIMIQs